The δ18O and δ2H of water in the leaf growth‐and‐differentiation zone of grasses is close to source water in both humid and dry atmospheres. Issue 4 (3rd April 2017) - Liu, Hai Tao; Schäufele, Rudi; Gong, Xiao Ying; Schnyder, Hans
Summary: The oxygen and hydrogen isotope composition of water in the leaf growth‐and‐differentiation zone, LGDZ, (δ 18 OLGDZ, δ 2 HLGDZ ) of grasses influences the isotopic composition of leaf cellulose (oxygen) and wax (hydrogen) – important for understanding (paleo)environmental and physiological information contained in these biological archives – but is presently unknown. This work determined δ 18 OLGDZ and δ 2 HLGDZ, 18 O‐ and 2 H‐enrichment of LGDZ (∆ 18 OLGDZ and ∆ 2 HLGDZ ), and the 18 O‐ and 2 H‐enrichment of leaf blade water (∆ 18 OLW, ∆ 2 HLW ) in two C3 and three C4 grasses grown at high and low vapor pressure deficit (VPD). The proportion of unenriched water ( p x ) in the LGDZ ranged from 0.9 to 1.0 for 18 O and 1.0 to 1.2 for 2 H. VPD had no effect on the proportion of 18 O‐ and 2 H‐enriched water in the LGDZ, and species effects were small or nonsignificant. Deuterium discrimination caused depletion of 2 H in LGDZ water, increasing (apparent) p x ‐values > 1.0 in some cases. The isotopic composition of water in the LGDZ was close to that of source water, independent of VPD and much less enriched than previously supposed, but similar to reported xylem water in trees. The well‐constrained p x will be useful in future investigations of oxygen and hydrogen isotopic fractionation during cellulose and wax synthesis, respectively.